Gillnet colour affects catch efficiency in pearlspot (Etroplus suratensis) tropical estuary fishery - Kristine Cerbule; V.R. Madhu; Salini Mohanan; Bent Herrmann (Aquaculture and Fisheries)
Gillnets are one of the most commonly used fishing gears in both marine and inland waters. Different colour filament nettings are often used in gillnets. However, the effect of gillnet colour on catch efficiency is unclear for most fisheries. Therefore, in this study we investigated the effect of gillnet colour on the catch efficiency in pearlspot (Etroplus suratensis) fishery in Vembanad lake, India. Gillnet colours tested were transparent, green and blue. Results showed that in this fishery, the catch efficiency of gillnets of the three colours tested differed significantly. The highest catch efficiency of pearlspot was shown by green gillnets compared to transparent or blue netting. Specifically, green gillnets on average were estimated to be 74% more efficient compared to transparent gillnets. For the green compared to the blue gillnets, the catch efficiency was estimated to be higher by 81%. These results demonstrate that gillnet colour can be an important factor significantly affecting the catch efficiency of this fishing gear.